Manajemen Citra Politik Prabowo Subianto Dan Sandiaga Uno Melalui Akun @Prabowo Dan @Sandiuno - Silvanus Alvin (Komunika, 2019)
The purpose of the research is to show the political impression management of the president and vice president candidates, Prabowo Subianto and Sandiaga Uno in social media, in the presidential election 2019. Instagram is the focus of social media in the research. Specifically, the research would like to know the created impression in each Instagram account of the political figure, @Prabowo and @Sandiuno on August 10, 2018 to September 23, 2018. The method used in the research was content analysis method, which followed Simunjak Typology (2017) to know the candidate skills and virtues, disclosing private information, attacking political opponents, speaking in colloquial language, emphasizing particular issues. One of the interesting investigation results showed both Prabowo and Sandiaga used Instagram as a political tool to create their political impression as the religious candidates. Another result was Prabowo did not use his own social media account to offend his political rival, while Sandiaga offended incumbent candidates about the economic policy.